Comment on erratum to "Infrared absorption cross sections of isobutane with hydrogen and nitrogen as broadening gases J Quant Spectrosc Radiat Transf 227 (2019) 226-229", J Quant Spectrosc Radiat Transf 242 (2020) 106771. (October 2021) - Bernath, P.F.
Highlights: PNNL infrared absorption cross sections for isobutane are correct. A recent erratum casting doubt on the PNNL data is incorrect. Corrected isobutane cross sections are provided.